Comparative evaluation of the efficacy of three GnRH analogues in induced breeding of stinging catfish, Heteropneustes fossilis under hatchery conditions - Yasmin, Rahima; Rahman, Md. Mofizur; Chakraborty, Smriti; Sarker, Bhakta Supratim; Bappy, Md. Maheen Mahmud; Sarker, Pallab Kumer; Albeshr, Mohammed Fahad; Arai, Takaomi; Hossain, M. Belal (Frontiers in Sustainable Food Systems, 2024)
Evaluating the breeding performance of cultivable fish using gonadotropin-releasing hormone (GnRH) analogues is crucial for optimizing reproductive efficiency and enhancing the sustainability of aquaculture practices. However, there is a lack of understanding regarding which GnRH analogue performs best under hatchery conditions for stinging catfish. Therefore, this study was conducted to assess the breeding performance of stinging catfish (Heteropneustes fossilis) using three commercially available GnRH analogues: Wova-FH, Ovaprim, and Easy-spawn. For this purpose, an experiment was set up in a commercial hatchery by dividing the samples into three groups, each treated with one of the analogues: Wova-FH, Ovaprim, or Easy-spawn. In the experiment, a ratio of 1.5:1 male to female was maintained, and 1 ml syringes were used to inject the analogues. The results showed that the spawning induction efficiency differed among the three inducing agents. Compared to Ovaprim and Easy-spawn, Wova-FH-treated H. fossilis exhibited higher breeding success in all measured aspects. Specifically, Wova-FH achieved a latency period of 8 hours, an ovulation rate of 87.25%, a fertilization rate of 89.33%, a hatching rate of 88.85%, and an incubation period of 16 hours. In comparison, Ovaprim and Easy-spawn had incubation periods of 18 hours and 24 hours, respectively. In Ovaprim-induced individuals, the latency period was approximately 8.30 hours, with an ovulation rate of 82.08%, a fertilization rate of 86.75%, and a hatching rate of 85.97%. In contrast, the Easy-spawn-induced individuals had a latency period of 9 hours, an ovulation rate of 27.50%, a fertilization rate of 27.10%, and a hatching rate of 26.15%. Significant differences (p<0.05) were observed among the treatments in both the ovulation rate, fertilization rate, latency period incubation period, and hatching rate. The findings suggest that Wova-FH is a superior alternative to Ovaprim and Easy-spawn for GnRH analogues in the induced breeding programs of H. fossilis, offering optimal yield.